Modeling the impact of air void heterogeneity in the response of asphalt mixtures subjected to mechanical-environmental degradation processes (2016)
The objective of this dissertation is to study the uncertainty in the performance of Hot Mix Asphalt (HMA) through the use of computational approaches that effectively consider the inherent heterogeneity of the material when it is subjected to different mechanical and environmental conditions. Two modeling scales are herein considered: the macro scale and the micro scale. Macro mechanical modeling constitutes the simplest modeling methodology in Pavement Engineering, and it is usually used when studying the overall response of complete pavement structures. On the contrary, in the micro mechanical approach the internal structure of the material is modeled with a greater degree of detail (i.e. by explicitly including aggregates and/or characteristics of the air void phase) and both macro and micro or localized effects are characterized and analyzed. At the macro scale, material heterogeneity is characterized indirectly through the Air Void (AV) content of the asphalt mixtures by means of a stochastic tool called random fields, while at the micro scale such heterogeneity is captured via the detailed geometric depiction of the air void and the aggregate phases within the microstructure of the mixture